On the convergence of a perturbation series solution for reflection from periodic rough surfaces. - Rosich, R.K (IEEE Transactions on antennas and propagation)
In 1977, Rosich and Wait (see Radio Science, vol.12, no.5, p.719-29, Sept./Oct. 1977) presented a general expression for a perturbation series solution to electromagnetic (EM) reflection from an imperfectly conducting periodic rough surface. This is the first known publication of such a general result. Although this expression was shown to be consistent with earlier published results, all questions concerning the convergence of the series were deferred. This paper takes a first step in addressing this oversight